Hubungan Antara Teknologi Hijau, Insentif Pajak Karbon, Dan Kepatuhan Perusahaan Terhadap Standar Akuntansi Karbon (Studi Kasus Pt. Citra Nusantara Energi) - Laila, Amar'atus; Ramadhanti, Nouva Ayu; Putri, Aprilia Wahana; Kurniawati, Aprilia Tri; R. Pandin, Maria Yovita (Jurnal Ekonomika Dan Bisnis (JEBS), 2025)
Global climate change poses a major challenge to the industrial sector, particularly the energy sector, which contributes approximately 24–25% of total global greenhouse gas emissions. To address this issue, the adoption of green technology and fiscal policies such as carbon tax incentives are expected to enhance corporate compliance with carbon accounting standards. This study aims to analyze the relationship between the use of green technology, the utilization of carbon tax incentives, and corporate compliance with carbon accounting standards, both partially and simultaneously. A quantitative approach with a causal-comparative research design was applied. Data were collected through questionnaires distributed to 50 employees of PT. Citra Nusantara Energi and analyzed using multiple linear regression, supported by validity and reliability tests, classical assumption tests, t-tests, and F-tests. The results show that green technology and carbon tax incentives have a significant partial effect on carbon accounting standards, while corporate compliance does not. However, simultaneously, the three independent variables significantly influence carbon accounting standards. These findings highlight the importance of environmentally friendly technology adoption and fiscal incentives in improving the transparency and accountability of corporate carbon emission reporting.